Teenage Emotions in Junior High School Students and Their Implications for Guidance and Counseling Services - Nurdiani Desra; Zikra Zikra (Jurnal Neo Konseling, 2019)
Anger is a form of negative emotions that is displayed in the form of behavior. This research is motivated by the phenomenon of students who are irritable, easily offended so as to say harshly and hit a friend. This study aims to describe the angry emotions of adolescents in junior high school students and their implications for guidance and counseling services. This research is a type of descriptive research using quantitative methods. The population of this study was 475 students and a sample of 217 students were selected using the Stratified Random Sampling technique. The instrument used was a questionnaire. The findings of this study indicate that, frist, teen angry emotions based on biological aspects tend to be in the quite high category, second, teen angry emotions based on emotional aspects tend to be in the high enough category, third, teen angry emotions based on intellectual aspects tend to be in the high category, fourth, teen angry emotions based on social aspects tend to be in the high enough category, fifth, teen angry emotions based on spiritual aspects tend to be in the quite high category.